THE TRANSLATION ANALYSIS OF IDIOMATIC EXPRESSIONS IN THE MOVIE OF AMERICAN PIE 6: THE BETA HOUSE - Wawa Puja Prabawa, - (2008)
Translating idioms is not an easy task because idioms have their own meanings, moreover in the movie. Thus, to translate idioms appropriately, a certain technique is needed so it can be understood by the viewers. In addition, deciding an appropriate word in translating idioms by using an appropriate method of translation becomes an important thing in doing the translation work. Considering that issue, the study conducted is entitled TRANSLATION ANALYSIS OF IDIOMATIC expressionS IN THE MOVIE OF AMERICAN PIE 6:THE BETA HOUSE which is aimed to find out the methods of translation employed by the translator in translating the idiomatic expressions and the types of idiomatic expressions which are mostly used in the movie. This study is a descriptive qualitative method. This method used to produce a systematic and factual description about the gained data. Meanwhile, the data were gathered by using the document analysis technique. The result of this study showed that several methods were applied in translating the idiomatic expressions: literal translation method, semantic translation method, communicative translation method and faithful translation method. Furthermore, from the six types of idiomatic expression, there were differences of the number of idiomatic expressions from one type into another. The findings of the research were finally concluded that types of idioms mostly used in the movie of American Pie 6: The Beta House